Re-reading Zaynab al-Ghazali's representations of the muslim women and Islamic feminism in the 21st Century (2011)
This paper focuses on the activism and feminism of the Egyptian Zaynab al-Ghazali al-Jubayli (1918-2009) in order to examine what she thought about Muslim women's roles in both the political and Islamic struggles of the Muslim Brotherhood in Egypt. Existing literature. whilst attesting to Zaynab al-Ghazali's eminent position in both contemporary Islamic circles and feminist discourses, fails to show how her feminist activities connected with the Muslim Brotherhood. By contrast with the secular feminist postulations of Muslim women like Ahmed Leila, Assia Djebar and Nawal Sa'dawi, this paper examines how Zaynab's feminist activism and the organisation of the Muslim Brotherhood connect in their da'wah approaches and contributions to the revivalism of 'authentic" Islamic feminism in contemporary society. This paper is based upon Zaynab's autobiographical work, Ayyam min Hayati to show how Zaynab and her associates, using the Muslim Brotherhood's struggles, were able to employ the Islamic female agency even under the unfavourable brutal regime of the then Egyptian President, Jamal 'Abd an-Nasir (1956-1970).